The Relationship of Knowledge, Attitudes, and Scalp Care Behaviors to The Risk of Seborrheic Dermatitis in The Class of 2023 and 2024 Students of The Faculty of Medicine, Al-Azhar Islamic University In 2025 - Jannatul Ulya; Lysa Mariam; Rusmiatik (CV. Inara, 2026)
Background: Seborrheic dermatitis is a chronic inflammatory skin disease in areas rich in sebaceous glands, especially the scalp, which is influenced by the growth of Malassezia sp and risk factors such as knowledge, attitudes, and scalp care behavior. Objective: To determine the relationship between knowledge, attitudes, and scalp care behavior on the risk of seborrheic dermatitis in the 2023 and 2024 intakes of students at the Faculty of Medicine, Al-Azhar Islamic University in 2025. Methods: This study was a quantitative cross-sectional study with a purposive sampling design. Data were collected through questionnaires and clinical examinations, then analyzed bivariately using the Chi-square test with a significance level of p-value <0.05. Results: Most respondents were at risk of developing seborrheic dermatitis (67.5%). The Chi-square test results showed no relationship between scalp care knowledge and the risk of seborrheic dermatitis (p-value = 1.000; PR = 0.977), while attitudes (p-value = 0.000; PR = 0.257) and scalp care behavior (p-value = 0.000; PR = 0.075) were significantly related and acted as protective factors. Conclusion: There is no relationship between the level of knowledge of scalp care and the risk of seborrheic dermatitis, but attitudes and behavior of scalp care are significantly related to the incidence of seborrheic dermatitis in students of the Faculty of Medicine, Al-Azhar Islamic University.